RELIABILITY ANALYSIS OF RELAY PROTECTION DEVICES OF ELECTRICAL EQUIPMENT OF POWER PLANTS AND SUBSTATIONS - Федорів, Михайло; Курляк, Петро; Гладь, Іван; Бацала, Ярослав; Візнович, Віталій (Modern engineering and innovative technologies, 2025)
The article analyzes the reliability of relay protection devices of power plants and substations in power systems. It is shown that the need to take into account relay protection when assessing the reliability of power systems is due to the fact that a si